2022
DOI: 10.1007/s00603-022-02850-7
|View full text |Cite
|
Sign up to set email alerts
|

Semi-analytical Method for Modeling Wellbore Breakout Development

Abstract: Borehole breakout initiation, progression, and stabilization are modeled using a semi-analytical method based on Melentiev’s graphical conformal mapping procedure, and Kolosov–Muskhelishvili complex stress potentials. The only input data required are the elastic moduli of the rock, the Coulomb strength parameters (cohesion and angle of internal friction), and the far-field stresses. The stresses around the borehole wall are computed, the region in which the rock has failed is then “removed”, creating a new bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Breakout failure expands episodically with the separation of crushed rock layers until it reaches stability. The breakout failure zone is V shaped or dog eared and has two characteristics, width ( ) B θ and depth ( ) B r [32][33][34][35][36][37]. According to field reports, breakouts have been observed in different types of rocks such as limestone, siltstone, granite, dolomite and sandstone [38][39][40].…”
Section: Breakout Wellboresmentioning
confidence: 99%
“…Breakout failure expands episodically with the separation of crushed rock layers until it reaches stability. The breakout failure zone is V shaped or dog eared and has two characteristics, width ( ) B θ and depth ( ) B r [32][33][34][35][36][37]. According to field reports, breakouts have been observed in different types of rocks such as limestone, siltstone, granite, dolomite and sandstone [38][39][40].…”
Section: Breakout Wellboresmentioning
confidence: 99%
“…Setiawan and Zimmerman [33] presented a semianalytical method to investigate breakout progression and stabilization using the conformal mapping procedure, and the analysis carried out by them led to a correlation between the breakout geometry, the properties of the rock materials, and the in situ stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies are divided into two categories; studies based on the discrete element method (Cook et al, 2004;Potyondy & Cundall, 2004;Li et al, 2006;Rahmati et al, 2021) and studies based on the finite element method (Bahrehdar & Lakirouhani, 2022;Jolfaei & Lakirouhani, 2022). Setiawan and Zimmerman (2022) presented a semi-analytical method to investigate the episodic breakout progression by means of the conformal mapping procedure, the analysis carried out by them led to a correlation between the breakout geometry and the in situ stresses. Bahrehdar and Lakirouhani (2023) investigated the effect of the eccentricity of the borehole on the breakout dimensions using the finite element method and concluded that for boreholes with different eccentricities, the stress concentration factor at the breakout tip becomes the same in the last step of expansion.…”
Section: Introductionmentioning
confidence: 99%